Gaya Komunikasi Guru dalam Mewujudkan Kesantunan Berbahasa pada Anak Usia Dini di SD Inpres 195 Kampung Beru Kabupaten Takalar - Wahyuni, Nur; Usman, Usman; Azis, Abdul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the types of communication styles used by teachers in realizing politeness in early childhood at SD Inpres 195 Kampung Beru, Takalar Regency. This study uses a descriptive qualitative method. Data were collected through observation, interviews, and voice recording. The sampling technique used was purposive sampling, with the research subjects being one grade 1 teacher and her students who were in the early age range (6–7 years). The study was conducted for one week in December 2024. The results showed that teachers used six types of communication styles, namely friendly or friendly, short and concise, attentive, lively and animated, relaxed, and dramatic. Each communication style has a significant influence on the formation of students' politeness. A friendly, attentive, and lively communication style encourages students to speak politely, confidently, and respect others. This study makes an important contribution to the development of teacher communication strategies, especially at the early childhood education level.